Consulting the Conference of Rulers under the Federal Constitution - Das, Dato’ Cyrus (Journal of Malaysian and Comparative Law, 2019)
The Conference of Rulers has been described as the most prestigious body in the country. This observation by Tun Suffian is understandable from the standpoint of the status of the body because it comprises of the nine Sultans and the four Governors who are the constitutional heads of government in their respective States.